Enhancing Governance in Chinese Football Characteristic Schools: A Collaborative Approach to Overcome Challenges and Promote Sports Development - Wu Yang (International Journal of Education and Humanities, 2025)
The governance of Chinese Football Characteristic Schools (CFCS) faces multiple challenges that hinder their ability to contribute to football development in China. Using a literature review method, this study identifies key issues, including low family participation, insufficient football fields per capita in schools, inadequate core competencies of teachers, ineffective utilization of football-specific funds, a lack of influence from social organizations, and mutual distrust among stakeholders. These issues collectively limit the effectiveness of governance in CFCS. The study emphasizes the importance of adopting a collaborative governance framework to address these challenges. Collaborative governance, which integrates efforts from families, schools, and society, aligns with contemporary demands for more participatory and inclusive management practices. By enhancing family participation, leveraging resource utilization, and fostering trust among stakeholders, this approach aims to construct an effective engine for governance. Moreover, it advocates for targeted improvements, such as increasing teacher training, optimizing resource allocation, and promoting the active involvement of social organizations to ensure that governance is efficient and sustainable. The findings underscore the urgent need for reform in the governance model of CFCS to support the high-quality development of China’s sports industry. The study concludes with recommendations to institutionalize collaboration, enhance stakeholder communication, and implement evidence-based strategies to overcome existing barriers. These measures can help CFCS play a pivotal role in cultivating football talent and advancing China's sports enterprises in line with national development goals. By building a robust and collaborative governance model, CFCS can realize its full potential in driving sports excellence